Analisis Konten TikTok Dalam Komunikasi Politik Capres-Cawapres di Pemilu 2024 untuk Generasi Z: Pendekatan Teori Media Baru dalam Menganalisis Konten Tiktok - Makarawung, Yehezkiel Andreas; Wulandari, Yulianti Fajar; Himawan, Sultan (Brand Communication, 2024)
Analyze TikTok content in the Political Communication of Presidential and Vice Presidential Candidates with a focus on "Generation Z". This study analyzes TikTok content in the political communication of presidential and vice presidential candidates in the 2024 Election using the new media method by Pierre Levy, focusing on Generation Z. Generation Z, as digital natives, has unique characteristics in consuming political information through social media such as TikTok. This study uses a qualitative approach and content analysis to explore how presidential and vice presidential candidates use TikTok to convey political messages, build images, and influence public opinion. Data were collected from the official TikTok accounts of presidential and vice presidential candidates during the campaign period. The results of the study show that TikTok is effective in attracting the attention of Generation Z through creative, concise, and easy-to-understand content. Visual elements, the use of popular music, and direct interaction increase political participation and engagement of Generation Z. This study provides important insights for political communication strategies in the digital era, as well as practical demonstrations for politicians in designing more effective and inclusive campaigns.